Can agricultural traders be trusted? Evidence from urban coffee markets in Ethiopia - Assefa, Thomas; Minten, Bart (International Food Policy Research Institute, 2015)
Traditional food marketing systems in developing countries are often not trusted. In consequence, policy makers frequently try to regulate them and modern market arrangements increasingly are emerging to address some of their presumed deficiencies. However, it is unclear how trustworthy these markets actually are and if and to what extent regulation and modernization affects market governance. In this paper we look at the case of coffee in urban settings in Ethiopia to test trustworthiness along three dimensions of trade transactions - weights, quality, and the presence of illegal trade. We find that traders are relatively trustworthy on observable quality characteristics and weights.